Korean Women in Leadership (Current Perspectives on Asian Women in Leadership, 2018)
The book focuses on the historical, political, economic, and cultural elements of Korea and the strong influence these have on women leaders in the nation. Gender inequality and underutilization of female talent are deeply rooted and widespread in Korean society, and women's appointment to high-ranking leadership roles is extremely challenging due to their inferior status to men. This book addresses the development and participation of women leaders at the organizational level, exposing the global gender gap and dominant western values from a uniquely Korean perspective. .